What is being done to respond to the rise of chronic diseases and multi-morbidity in Czechia, Hungary, Poland, and Slovakia? - Sagan, Anna; Kowalska-Bobko, Iwona; Bryndová, Lucie; Smatana, Martin; Chaklosh, Ihor; Gaál, Pétér (Frontiers in public health, 2022)
Although countries in central and eastern Europe (CEE) have relatively younger populations compared to the West, their populations are often affected by higher prevalence of chronic conditions and multi-morbidity and this burden will likely increase as their populations age. Relatively little is known about how these countries cater to the needs of complex patients. This Perspective piece identifies key initiatives to improve coordination of care in Czechia, Hungary, Poland, and Slovakia, including some pioneering and far-reaching approaches. Unfortunately, some of them have failed to be implemented, but a recent strategic commitment to care coordination in some of these countries and the dedication to rebuilding stronger health systems after the COVID-19 pandemic offer an opportunity to take stock of these past and ongoing experiences and push for more progress in this area.
Keywords: care coordination; multi-morbidity; Polsko; chronic disease; Slovakia; lidé; COVID-19; pandemie; Czech Republic; Czechia; Hungary; Česká republika; chronická nemoc; Slovenská republika; Multimorbidity; Maďarsko; Poland; Chronic Disease; multimorbidita; Pandemics; integrated care; Humans